(untitled) - Guru, Bhag S. (Cambridge, UK, 2004)
Including examples and problems throughout and background revision material where appropriate, this book introduces undergraduate students to the basic concepts of electrostatic and magnetostatic fields. It also covers Maxwell's equations, propagation, transmission and radiation, and includes chapters on the Finite Element and Finite Difference method. A CD containing many MathCad examples is included with the book, and a comprehensive solutions set is also available.
Keywords: Electromagnetic fields,Điện từ trường